Promoting maize technology transfer in West and Central Africa: a networking approach - Badu-Apraku, Baffour; Fakorede, M.A.B.; Ajala, S.O. (2003)
The major thrust of the West and Central Africa Collaborative Maize Research Network (WECAMAN) has been on the development of early and extra-early maize varieties and associated agronomic practices. Adoption of these varieties and, to some extent, the complementary agronomic practices by farmers has led to the expansion of maize production in the sub region. However, the rate of adoption of the technologies has been constrained by several factors, including high price and non-availability of inputs, poor seed production and distribution, inadequate on-farm testing of available technologies, inadequate number of extension workers and poor researcher-extension farmer linkages. We discuss herein the strategy employed by WECAMAN to facilitate better adoption of the technologies. The strategy includes the commissioning of studies on alternative methods of soil management, development of community seed production schemes, use of farmer participatory methods and the production test plot (PTP) as tools to test and demonstrate new technologies, and strengthening research-extension farmer linkages. The network also funded marketing studies to document the evolution of domestic maize production and how it can be used to influence policy in WECAMAN member countries. The payoff is that during the last two decades of the 20th Century, maize production has increased dramatically in the sub region as a whole and in most of the individual member countries.